EVALUASI RENCANA TATA RUANG WILAYAH ( RTRW ) TERHADAP KAWASAN BENCANA BANJIR DI KABUPATEN DHARMASRAYA - Ressa Andriani Andriani; Iswandi Umar (JURUSAN GEOGRAFI FIS UNP, 2021)
The purpose of this study was to (1) determine the level of flood hazard to existing conditions in Dharmasraya Regency (2) to determine the implementation of RTRW in Dharmasraya Regency (3) to determine the level of flood hazard to RTRW in Dharmasraya Regency by using an overlay method carried out on each parameter used as a reference in making flood-prone to the conditions of existing land use and RTRW. The results showed 1) The most dominant flood-prone area in Dharmasraya Regency was moderate covering an area of ​​1886,98 Km2 or 61,81% and a high area of ​​512,55 Km2 or 16,78 %, while the prone to flooding on land use conditions with a high classification of use The land is a plantation area of ​​395,42 Km2 and prone to low classification, namely ponds & ponds and lakes. 2) The implementation of the appropriate RTRW consists of 6 spatial patterns, namely forests, plantations, settlements, rice fields, riparian areas and moor / fields. 3) Flood-prone to RTRW conditions with a high disaster-prone classification with the most extensive designation, namely plantations covering an area of ​​235,15 km2 and low classification, namely reservoirs & ponds.